C-reactive protein in acute pulmonary embolism - (:unkn) unknown (BMJ Publishing Group, 2011)
Background: Right ventricular dysfunction and N-terminal proB-type natriuretic peptide (NT-proBNP) are established determinants of prognosis in acute pulmonary embolism (PE). The aim of the study was to investigate the prognostic value of C-reactive protein (CRP) in PE. Methods: Fifty-six patients (mean age, 64.4 ± 14.8years; 22 male subjects) with acute PE were consecutively enrolled and followed for 36 months after discharge. Serum CRP, NT-proBNP, and troponin T levels were determined. Right ventricular function was evaluated by transthoracic echocardiography. Results: Right ventricular dysfunction was present in 31 patients and was more frequent in patients with higher CRP and NT-proBNP levels (P = 0.020 and P = 0.045, respectively). During the 36-month follow-up, there were 15 terminal events (death due to recurrent PE). The mortality rate was 41.2% in patients with NT-proBNP levels greater than 1000 pg/mL, whereas it was 5.9% in patients with less than 500 pg/mL (P = 0.011). Mortality rates also were higher in patients with elevated CRP and troponin T levels, but the differences did not reach clinical significance. The survival rate of acute PE patients with lower NT-proBNP and CRP levels was better than that of patients with higher NT-proBNP and CRP levels. Receiver operating characteristic curve analysis demonstrated cutoff values for NT-proBNP as 1800 pg/mL (sensitivity, 93.3%; specificity, 68.2%; positive predictive values, 66.7%; and negative predictive values, 93.8%) and for CRP as 48mg/L (sensitivity, 72.7%; specificity, 61.9%; positive predictive values, 50.0%; and negative predictive values, 81.3%) to predict mortality in PE patients. Conclusions: C-reactive protein is associated with right ventricular dysfunction, which is a predictor of prognosis in PE and may become a promising biomarker for risk stratification of PE, although CRP is not found superior to NT-proBNP. Copyright © 2011 American Federation for Medical Research..
Keywords: C-reactive protein; Inflammation; N-terminal proB-type natriuretic peptide; Prognosis; Pulmonary embolism; Right ventricular dysfunction; Survival